The ways of rising the role of information and consulting in agricultural development of Republic of Armenia - Казарян, А. Р.; Бадалян, М. Э. (Scientific Progress & Innovations, 2012)
Agricultural enterprising mostly depends on effective functioning of formative and consulting system. At present time argicultural production in Armenia has a law level. This with other reasons is caused by imperfection of informative and consulting system. For effective work of this service it is necessary to enlarge its network, activate the work of scientific and educational institutions, to rise the level of the state support and make the role of television more important.